Ten-year follow-up after 96 weeks treatment with Peginterferon plus tenofovir in Hepatitis D (HIDIT-II): improved clinical outcome after combination therapy - Yurdaydin, Cihan; Kahlhöfer, Julia; Caruntu, Florin Alexandru; Yalcin, Kendal; Gürel, Selim; Akarca, Ulus S.; Sprinzl, Kathrin; Bock, Hans H.; Bockmann, Jan-Hendrik; Papatheodoridis, George V.; Merle, Uta; Demir, Münevver; et al. (United european gastroenterology journal, 2026)
Background Chronic delta hepatitis represents a major health burden. Until recently, pegylated interferon-alfa-2a (PEG-IFNα) therapy was the only treatment option for patients infected with hepatitis D virus (HDV). The aim of this study was to evaluate 10-year long-term clinical and virological outcomes after 96 weeks of treatment with PEG-IFNα with or without tenofovir disoproxil fumarate (TDF). Methods We conducted a retrospective follow-up study of the Hep-Net-International-Delta-Hepatitis-Intervention-Study 2 (HIDIT-II trial). Patients had received 96 weeks of treatment with either PEG-IFNα-2a plus TDF or PEG-IFNα-2a alone. Patients were included if they had completed the 96-week treatment period and had at least one follow-up visit (PEG-IFNα-2a + TDF; n = 51, PEG-IFNα-2a alone; n = 56). Results Patients who received PEG-IFNα-2a + TDF were younger (37 vs. 42 years) and no significant differences were observed in other baseline characteristics between the two treatment arms. A total of 26 patients (24%) developed one or more liver-related endpoints after a mean time of 8.4 years. The incidence of endpoints was significantly lower in the combination group (14% vs. 34%, p = 0.02). The development of liver-related endpoints was also associated with non-response to therapy (HDV RNA and HBsAg), elevated HBV DNA at week 72, and baseline age, cirrhosis, platelets, INR, AST, GGT, bilirubin and albumin according to the Cox regression model. Conclusions The long-term follow-up of this large randomised clinical trial demonstrates that combination therapy with TDF and virological response to PEG-IFNα-2a (undetectable HDV RNA and HBsAg loss) were associated with better clinical outcomes. Trial Registration NCT00932971, EudraCT 2008-005560-13
Zuerst veröffentlicht: 29. November 2025
Gesehen am 30.01.2026